Dapagliflozin Attenuates Myocardial Fibrosis by Inhibiting the TGF-β1/Smad Signaling Pathway in a Normoglycemic Rabbit Model of Chronic Heart Failure - Chen, Xuefeng; Yang, Qian; Bai, Wenlou; Yao, Wenjing; Liu, Litian; Xing, Yuanyuan; Meng, Cunliang; Qi, Peng; Dang, Yi; Qi, Xiaoyong (Frontiers in Pharmacology, 2022)
Recent studies have shown that sodium-glucose cotransporter-2 (SGLT2) inhibitors play a beneficial role for normoglycemic patients with heart failure (HF). However, the underlying mechanism remains largely unexplored. In the present study, we aimed to investigate the cardioprotective effect of SGLT2 inhibitors in a normoglycemic rabbit model of chronic heart failure (CHF), and its potential mechanism was also explored. A total of 24 male New Zealand white rabbits were randomly divided into sham group, HF group, perindopril group, and dapagliflozin (DAPA) group. The normoglycemic CHF model was established by aortic constriction for 12 weeks. In the 13th week, DAPA (1 mg/kg/day) or perindopril (0.5 mg/kg/day) was administered by oral gavage daily for 10 weeks. Both the sham group and HF group were given normal saline via gavage. After 10 weeks, the heart structure and function were evaluated by echocardiography and plasma NT-proBNP. Moreover, cardiac fibrosis was analyzed using immunohistochemistry, Masson’s trichrome staining, and Western blotting analysis. Results showed that DAPA improved the myocardial structure and function of normoglycemic CHF rabbits and ameliorated myocardial fibrosis. Further study indicated that DAPA suppressed cardiac fibrosis by inhibiting the transforming growth factor β1 (TGF-β1)/Smad signaling pathway. Collectively, our findings showed that DAPA could ameliorate cardiac fibrosis in normoglycemic CHF rabbits by inhibiting the TGF-β1/Smad signaling pathway.